2008
DOI: 10.1103/physrevd.78.064070
|View full text |Cite
|
Sign up to set email alerts
|

Barbero-Immirzi parameter as a scalar field:K-inflation from loop quantum gravity?

Abstract: We consider a loop-quantum gravity inspired modification of general relativity, where the Holst action is generalized by making the Barbero-Immirzi (BI) parameter a scalar field, whose value could be dynamically determined. The modified theory leads to a non-zero torsion tensor that corrects the field equations through quadratic first-derivatives of the BI field. Such a correction is equivalent to general relativity in the presence of a scalar field with non-trivial kinetic energy. This stress-energy of this f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
262
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(272 citation statements)
references
References 17 publications
9
262
0
1
Order By: Relevance
“…Simulations [21,22,23] have shown that effective equations approximate very well the full quantum dynamics (in the sense of expectation values of Dirac observables). The effective Hamiltonian constraint is, for N=1 corresponding to cosmic time t,…”
Section: A Bouncing Universementioning
confidence: 99%
“…Simulations [21,22,23] have shown that effective equations approximate very well the full quantum dynamics (in the sense of expectation values of Dirac observables). The effective Hamiltonian constraint is, for N=1 corresponding to cosmic time t,…”
Section: A Bouncing Universementioning
confidence: 99%
“…In particular, in [55] it was verified for ω = 1. Equation (19) corresponds to an ellipse in the plane (ρ, H), that we can parametrize in the following form…”
Section: Modified Friedmann Equationsmentioning
confidence: 98%
“…We studied only two limiting regimes: βM 4 ≫ 1 and βM 4 1. Before proceeding to the analysis of these two cases, we mention that, since Q, Θ exponentially diverge in the r * → ±∞ limits, it is not at all obvious that equations (17), (18) reduce to the form (19) and then that their solutions, in these limits, have the form (20), as we have assumed at the beginning of this section. Actually, Eq.…”
Section: Integration Of the Perturbation Equationsmentioning
confidence: 99%